Прогнозування палеорусел у карбоні південно-східної частини Дніпровсько-Донецької западини (за результатами сейсмофаціального аналізу) - Несіна, Н.І.; Маркова, Г.Г. (Геоінформатика, 2016)
Вивчення генези аномалій типу “вуглеводневий поклад” з використанням фізико-геологічної інтерпретації каротажних діаграм, структурно-числового моделювання та геоінформаційного робота зумовило необхідність формалізації, математизації і автоматизації процесу отримання стратиграфічних даних із застосуванням розрахункового модуля, що виконує функцію геохронографа. Основою геохронографа слугувала космо-фізична модель процесу еволюційного розвитку об’єктів Сонячної системи, яка створена з використанням досягнень теоретичної фізики і результатів астрономічних спостережень. За допомогою реперного геохронографа в межах дослідженої площі висвітлено активність екзогенно-ендогенних процесів, обчислено час формування і тривалість існування водонафтогазоносних осадових товщ, ідентифіковано як нестаціонарний фізико-геологічний процес гідродинамічну пастку рециркуляційного типу. Отримані відомості доцільно використовувати для виявлення та дослідження зв’язків між розподілом і мінливістю у часі фізичних параметрів водо- та нафтогазоносних осадових товщ, часу появи і зникнення скупчень вуглеводнів та природиинестабільності величини їх запасів. Изучение генезиса аномалий типа “углеводородная залежь” с использованием физико-геологической интерпретации каротажных диаграмм, структурно-числового моделирования и геоинформационного робота обусловило необходимость формализации, математизации и автоматизации процесса получения стратиграфических данных с применением расчетного модуля, выполняющего функцию геохронографа. Основой геохронографа послужила космофизическая модель процесса эволюционного развития объектов Солнечной системы, которая создана с использованием достижений теоретической физики и результатов астрономических наблюдений. С помощью реперного геохронографа в пределах исследованной площади освещена активность экзогенно-эндогенных процессов, вычислены время формирования и продолжительность существования водонефтегазоносних осадочных толщ, идентифицирована как нестационарный физико-геологический процесс гидродинамическая ловушка рециркуляционного типа. Полученные сведения целесообразно использовать для выявления и исследования связей между распределением и изменчивостью во времени физических параметров водо- и нефтегазоносных осадочных толщ, времени появления и исчезновения скоплений углеводородов и природы нестабильности величины их запасов. The purpose of the paper is to give a detailed study of a deposit-type anomaly and hydrodynamic trap of the recycling type using a geo-information robot; to formalize, mathematize and automatize the stratigraphic data generation process; to create a calculation module which acts as a geochronograph; to get digital data and a graphic display of geoinformation about time, required to satisfy demand for petroleum exploration practice.
Design/methodology/approach. The method used is physical and geological well log interpretation, structural and numerical modeling, and creation of geoinformation digital technology based on it. This technology is based on exponential model of the Earth formation process applying time arrow. We also employed automatized measurement of time applying a datum geochronograph.
Findings. Based on the theoretical physics and astronomical observation data, we created a cosmophysical model of the evolutionary growth process of objects in the planetary system. By applying this cosmophysical model, a datum geochronograph was designed. Using this datum geochronograph within the examined area, the increase of the planet radius during the time and speed of its growth were detected, and the kinematic parameters of the process of the sedimentary cover formation were defined. Also the activity and intensity of exogenous-endogenous processes was analyzed. The time of formation and continuance of the existence of water oil and gas sedimentary rocks, the hydrodynamic trap of the recycling type, was identified as a non-stationary physics and geological process.
Practical value/implications. Evidence on unobservable and non-measurable time characteristics of the Earth’s interior unknown before was obtained in an automated way. This information can extend the theoretical and practical possibilities of stratigraphy by quantitative measurement of time. The generated system of spatiotemporal data should be used to find the existing relationships between the distribution and variability of the physical properties of water and oil and gas bearing sedimentary rocks, to determine the beginning of the formation of potential and well-known hydrocarbon accumulations, and the evolution of the saturation nature and value of reserves. It is expected that the obtained geoinformation will help to raise the level of general geological understanding and the efficiency of hydrocarbon exploration.